Women abuse as expressed in Tshivenda female songs - Rabothata, Thambatshira Tannie (University of Limpopo (Turfloop Campus), 2005)
This study investigates the expression of women abuse through female songs. Groups of singers from twenty-two communities were listened to during the study. A qualitative analysis was undertaken. Songs obtained from secondary sources, were compared and analysed in the same way in which those obtained from the singers themselves were analysed. In particular, the usefulness of these singing groups was examined. It was found that most of the women who are experiencing abuse of some kind, derive perceived social support from fellow singers. All the women in the different singing groups declared that they were not singing for the sake of singing but that they were sending messages to the perpetrators of abuse in the expectation that a change will be realized. Singing groups were found to be effectively providing assistance in dealing with emotional abuse. The study thus illuminates the subjective use of referential expressions in expressing abuse. This emphasizes the challenge for singers to check whether or not the manner in which they present their pleas is appropriate.
Thesis (Ph.D. (African Languages)) --University of Limpopo, 2005
Keywords: Women abuse; Venda Female songs; 362.82920968; Abused women; Venda (African people); Expressionism (Music) -- South Africa; Folk-songs -- South Africa -- Limpopo